(untitled) (Anclajes, 2019)
Sexual desire in women with functional diversity has hardly been portrayed in films in such an explicit way as in Oasis (Oasiseu, 2012), a raw and romantic drama in equal measure directed by the South Korean auteur Lee Chang-Dong. Through the female protagonist, a young woman with severe cerebral palsy who is confined in her apartment and subject to family and social exclusion, Lee Chang-dong offers a real-life moving portrait of functional diversity. The film denounces prejudices and social stereotypes and dismantles normative femininity, which assumes that a functionally diverse woman possesses an asexual body.